Two Arabidopsis Chloroplast GrpE Homologues Exhibit Distinct Biological Activities and Can Form Homo- and Hetero-Oligomers - Su, Pai-Hsiang; Lin, Hsuan-Yu; Lai, Yen-Hsun (Frontiers in Plant Science, 2020)
Flowering plants have evolved two distinct clades of chloroplast GrpE homologues (CGEs), which are the nucleotide exchange factor for Hsp70. In Arabidopsis, they are named AtCGE1 (At5G17710) and AtCGE2 (At1g36390). Characterization of their corresponding T-DNA insertion mutants revealed that there is no visible change in phenotype except a defect in protein import in an AtCGE2-knockout mutant under normal growth conditions. However, the embryo development of an AtCGE1-knockout mutant was arrested early at the globular stage. An AtCGE1-knockdown mutant, harboring a T-DNA insertion in the 5′-UTR region, exhibited growth retardation and protein import defect, and its mutant phenotypes became more severe when AtCGE2 was further knocked out. Sub-organellar distribution implied that AtCGE2 might be important for membrane biology due to its preferential association with chloroplast membranes. Biochemical studies and complementation tests showed that only AtCGE1, but not AtCGE2, can effectively rescue the heat-sensitive phenotype of Escherichia coli grpE mutant and robustly stimulate the refolding of denatured luciferase by DnaK. Interestingly, AtCGE1 and AtCGE2 are tending to form heterocomplexes, which exhibit comparable co-chaperone activity to AtCGE1 homocomplexes. Our data indicate that AtCGE1 is the principle functional homologue of GrpE. The possibility that AtCGE2 has a subsidiary or regulatory function through homo- and/or hetero- oligomerization is discussed.